Status Keberlanjutan Ekologi pada Pengelolaan Lubang Resapan Biopori di Kelurahan Langkapura Kecamatan Langkapura Kota Bandar Lampung - Tri Mulyaningsih; P Purwanto; Dwi P Sasongko (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2014)
Status of Ecological Sustainability in The Management of Biopore Infiltration Hole  in Langkapura Village, Langkapura District, Bandar Lampung City. Management of Biopore Infiltration Hole (BIH) is an activity undertaken as an effort to reduce the vulnerability of flooding and drought, also reducing the debit of rubbish in Bandar Lampung city. This study conducted in July to August 2014, in Langkapura village, Langkapura district, Bandar Lampung city. The aims of the study are; to know the physical and chemical soil BIH area, to analyze the index and sustainability status of ecological dimensions, and to analyze the sensitive attributes of ecological dimension through the sustainability BIH management. The analytical method used is MDS analysis ( Multidimensional Scaling ) with Rap-Biopore approach which modified from Rapfish analysis . The analysis stage is using MDS with Rap-Biopore approach which include; scoring attributes BIH management, MDS ordination determination , sensitivity analysis (Leverage) , and Monte Carlo analysis. The results of the research; (1) The physical condition of the soil is predominantly blocky clay soil structure, texture (sand 20.47%, dust 25.91%, 53.62% clay); permeability 0:14 cm/h, porosity 57.73%, temperature 27 °C, (2) The chemical soil conditions pH 6.54 and the base saturation 34.66%; sustainability index value reach to 38.10, which the status of sustainability management from LRB is “less sustainable", (4) Attributes that  highly sensitive through sustainability management LRB are rainfall and groundwater quality.